Theoretical review on bullying in students with specific educational support needs - Gómez Domínguez, María Teresa (2017)
This study presents a body of research showing the higher incidence of students with specific educational support needs to suffer bullying situations at school, both in their role as victims and as bullies. In conclusion, there is a need to address methodological changes, as well as to incorporate school violence prevention programs.